2004
DOI: 10.1097/00004872-200405000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone antagonist facilitates the cardioprotective effects of angiotensin receptor blockers in hypertensive rats

Abstract: These results demonstrate that residual aldosterone has a significant impact on target-organ damage in hypertension, even during chronic administration of an ARB. The addition of an aldosterone antagonist has an advantage in facilitating the cardioprotective effects of ARBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
2
18
1
Order By: Relevance
“…It has been reported that the combined treatment with an ARB and SPRL improves the expression of collagen mRNA and cardiac interstitial and perivascular fibrosis compared with both ARB and SPRL monotherapy in stroke-prone spontaneous hypertensive rats. 25 The RALES showed the clinical significance of SPRL in almost all patients with severe heart failure who were receiving an ACE inhibitor before the randomization, therefore, this evidence indicated the beneficial effects of the combined treatment of ACE inhibitor and SPRL. 11 Recently, Eplerenone Post-AMI Heart Failure Efficacy and Survival Study (EPHESUS trial) showed the efficacy of a new selective aldosterone blocker, eprelenone, in patients with heart failure.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that the combined treatment with an ARB and SPRL improves the expression of collagen mRNA and cardiac interstitial and perivascular fibrosis compared with both ARB and SPRL monotherapy in stroke-prone spontaneous hypertensive rats. 25 The RALES showed the clinical significance of SPRL in almost all patients with severe heart failure who were receiving an ACE inhibitor before the randomization, therefore, this evidence indicated the beneficial effects of the combined treatment of ACE inhibitor and SPRL. 11 Recently, Eplerenone Post-AMI Heart Failure Efficacy and Survival Study (EPHESUS trial) showed the efficacy of a new selective aldosterone blocker, eprelenone, in patients with heart failure.…”
Section: Discussionmentioning
confidence: 92%
“…The current understanding of the increasingly appreciated involvement of aldosterone in hypertension acting through BP elevation, vascular damage, and cardiac fibrosis and the realization that aldosterone has complex interactions with Ang II have provided justification for the use of combined angiotensin and mineralocorticoid blockade in the treatment of hypertension and cardiac failure. 76,77 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that ANG II is central in inflammatory processes (31). The treatment of the prehypertensive SHRs for 10 wk with losartan abolished or significantly ameliorated renal injury indicating a pivotal role in renal damage observed in SHRs.…”
mentioning
confidence: 92%